ANALYTIC HIERARCHY PROCESS DALAM PENGAMBILAN KEPUTUSAN TEMPAT KHUSUS PARKIR DI KABUPATEN CILACAP - Wijaya, Shadu Satwika; Rosyadi, Slamet; Atika, Zaula Rizqi; Sutikno, Chamid (Jurnal Inovasi Daerah, 2022)
The implementation of public services is the core business of public administration. In an effort to provide public services, local governments are required to pay more attention to public needs, one of which is the need for transportation. For this reason, accurate decision making is needed to ensure the effectiveness and efficiency of public administration. Cilacap is increasingly developing towards an industrial and service area so that community mobility is getting higher in line with economic movements. Therefore, there is a buildup and crowds in several areas that become agglomeration nodes caused by the presence of parking vehicles on the road. To prevent this buildup from increasing, local governments need to respond by providing parking building services. However, given the limited budget they have, the local government must make a decision to prioritize the construction of parking building services in the most feasible locations to be built. For this reason, this study aims to identify priority locations for special parking spaces in several Cilacap agglomeration areas, namely Majenang, Kroya and Cilacap Kota. Using by the Analytic Hierarchy Process method, results with high accuracy can be obtained in determining the priority of parking building service locations in Cilacap.